A citizen-centred approach to CSR in banking. Issue 4 (22nd October 2020) - van Hierden, Yannick Thomas; Dietrich, Timo; Rundle-Thiele, Sharyn
Abstract : Purpose: This study aims to demonstrate how banks can align their CSR investment to community needs and citizen preferences. A grounded theory inductive approach is applied to deliver a community-centred process that banks can apply to inform CSR investment decisions. Design/methodology/approach: This study employed a sequential mixed-method research design to identify areas of need from the perspective of community leaders and members through depth interviews. Following thematic analysis, citizen preferences for eight priority areas were elicited using best-worst scaling (BWS). Findings: Clear investment preferences emerged with citizens preferring six community investment causes, namely, (1) infrastructure, (2) crisis and prevention support, (3) community groups, (4) youth facilities and activities, (5) initiatives that support the local environment, and (6) physical activity promotion. The forming of community advisory committees emerged as one approach that banks could apply to ensure long-term citizen-centred CSR investment decisions. Research limitations/implications: This study is limited to one community and one community bank and a small convenience, cross-sectional data sample. Social implications: Community-oriented financial institutions should centre investment decisions on community need and citizen preferences ensuring investments made deliver the greatest societal benefit and community support for the banks is garnered. Originality/value: This paper provides important contributions to improve the effectiveness of CSR initiatives, providing an inductive, methodological approach that financial institutions can follow to better align their CSR investment to community needs and preferences.